2014
DOI: 10.1108/jima-01-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of mood on in-store behaviour among Muslim shoppers

Abstract: Purpose-The purpose of this paper is to examine the influence of atmospherics on in-store behaviour among Malay Muslim shoppers in Malaysia. The effect of age on shopping behaviour is tested using two age groups: 18-25 years and 50 years or older. Design/methodology/approach-Quantitative methodology was employed, using structural equation modelling for testing the hypotheses developed. Purposive sampling was applied. Findings-Results of the present study show that positive perceptions of atmospherics exerted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…In addition, mood research has proposed both the moderating (Bagozzi et al, 1999; Knowles et al, 1993; Prakash, 1985) and the mediating (Gardner, 1985; Knowles et al, 1993; Mattila and Enz, 2002) effects of mood. Empirical evidence has shown mood as either a moderator (Fedorikhin and Patrick, 2010) or a mediator (Leenders et al, 2016; Osman et al, 2013; Pugh, 2001). Although the mediating effect of mood has occasionally received no empirical support (Barger and Grandey, 2006; Bickart and Schwarz, 2001), measuring mood states after exposure to the service quality, this research finds the mediating role of mood on IB in a retail service encounter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mood research has proposed both the moderating (Bagozzi et al, 1999; Knowles et al, 1993; Prakash, 1985) and the mediating (Gardner, 1985; Knowles et al, 1993; Mattila and Enz, 2002) effects of mood. Empirical evidence has shown mood as either a moderator (Fedorikhin and Patrick, 2010) or a mediator (Leenders et al, 2016; Osman et al, 2013; Pugh, 2001). Although the mediating effect of mood has occasionally received no empirical support (Barger and Grandey, 2006; Bickart and Schwarz, 2001), measuring mood states after exposure to the service quality, this research finds the mediating role of mood on IB in a retail service encounter.…”
Section: Discussionmentioning
confidence: 99%
“…Mohan et al (2013) found that store environment perceptions elicited positive affect, which then encouraged IB. Osman et al (2013) showed that positive perceptions of atmospherics exerted a favorable influence on mood, which then affected in-store behavior in terms of expense amounts and revisit intentions. A store environment with more-attractive atmospheric factors (sensory stimuli and better services) increased IB by inducing more consumers’ pleasure (Kacen et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Visitors form attitude towards objects (Bagozzi, Gopinath, & Nyer, 1999). It is defined as the probability that a person will show a specific behavior in a particular situation (Osman, Ong, Othman, & Wei Khong., 2014;Osman, Alwi, & Khan., 2016). In retailing, 'affect' plays an integral role because of its inherent interpersonal context.…”
Section: ) Literature Reviewmentioning
confidence: 99%
“…When visitors hold a positive attitude towards technology, it significantly influences their behavior at shopping mall (Hwang, Kim & Lee., 2014) reflecting that attitude plays a mediating role in most cases. However, when examining attitude as a mediator, there exist mixed results; in belief-intention linkage, some studies reflect partial mediation of attitude whereas other show its full mediation (Hamari & Koivisto, 2015;Kim et al, 2017;Osman et al, 2014). Attitude influences visitors' evaluations related to objects and reflect a person's positive or negative assessment (Kim et al, 2009).…”
Section: ) Literature Reviewmentioning
confidence: 99%
“…This research sought to determine whether the entertainment and built environment act as mediators between ambiance and consumption. However, various studies have given the theoretical background of the relationship of entertainment and built environment on ambiance and consumption but none has used them as a mediator [60,[98][99][100][101]. Based on the literature review, we proposed that entertainment and built environment play as mediators between ambiance and consumption.…”
Section: The Mediating Effect Of Entertainment and Built Environmentmentioning
confidence: 99%